High risk cohort study for psychiatric disorders in childhood: rationale, design, methods and preliminary results. Issue 1 (3rd December 2014) - Salum, Giovanni Abrahão; Gadelha, Ary; Pan, Pedro Mario; Moriyama, Tais Silveira; Graeff‐Martins, Ana Soledade; Tamanaha, Ana Carina; Alvarenga, Pedro; Krieger, Fernanda Valle; Fleitlich‐Bilyk, Bacy; Jackowski, Andrea; Sato, João Ricardo; Brietzke, Elisa; et al.
Abstract The objective of this study is to present the rationale, methods, design and preliminary results from the High Risk Cohort Study for the Development of Childhood Psychiatric Disorders. We describe the sample selection and the components of each phases of the study, its instruments, tasks and procedures. Preliminary results are limited to the baseline phase and encompass: (i) the efficacy of the oversampling procedure used to increase the frequency of both child and family psychopathology; (ii) interrater reliability and (iii) the role of differential participation rate. A total of 9937 children from 57 schools participated in the screening procedures. From those 2512 (random =958; high risk =1554) were further evaluated with diagnostic instruments. The prevalence of any child mental disorder in the random strata and high‐risk strata was 19.9% and 29.7%. The oversampling procedure was successful in selecting a sample with higher family rates of any mental disorders according to diagnostic instruments. Interrater reliability (kappa) for the main diagnostic instrument range from 0.72 (hyperkinetic disorders) to 0.84 (emotional disorders). The screening instrument was successful in selecting a sub‐sample with "high risk" for developing mental disorders. This study may help advance the field of child psychiatry and ultimately provide useful clinical information. Copyright © 2014 John Wiley & Sons, Ltd.